New Ideas about Old Age Security : Toward Sustainable Pension Systems in the 21st Century - Holzmann, Robert; Stiglitz, Joseph E. (Washington, DC: World Bank, 2013)
Given the impact of the multipillar approach to pension reform and the diversity of its implementation, the authors, who presented papers at the 1999 conference on "New Ideas About Old Age Security," re-examine the evidence and thinking on pensions and retirement security. This report examines global issues on pension reform which help put in perspective three major sets of questions. A first set of questions deals with generic issues that concern policymakers worldwide, almost independently of apporaches to reform. Most prominent but also least understood are the economic policy questions regarding the economic circumstances that are most conducive to the initiation of a reform and to its eventual success. Equally important are questions relating to the coverage of the labor force under a reformed system. Other questions concern the distributive effects of reformed systems with respect to generation, income group, and gender. A second set of questions is linked with a move toward funded provisions under a multipillar approach. A third set of questions concerns the multipillar reform approach itself. A wide consensus has emerged inside and outside the World Bank about the multipillar framework, but that consensus does not extend to several key issues regarding how the framework should be implemented in practice. The introduction to this report sums up each chapter in the report and concludes with a discussion of policy issues and on areas requiring further research.